Qualidade ambiental no centro de Teresina. - Lopes, Lara Citó (2020)
Urban centers have been facing numerous problems as a result of urban planning that does not dialogue with the natural environment, presenting excessive consumption of resources. In this context, most urban plans and projects act with mitigating actions, disregarding the systemic view of the city, contributing to the occurrence of problems such as floods, traffic, temperature increase, among others. Because of this, people come to live in low quality environments. Thus, it is understood the urgency of reversing this situation, seeking to preserve the natural resources, fundamental to the functioning of cities, so that they can survive. For this, there is a great help tool: the green infrastructure. This, when implemented, has several benefits for the city due to the possibility of integration between ecosystems. Such a tool should appear as a guideline in urban plans and projects, as it assists in promoting environmental quality. It is also understood the real need for population participation and diagnosis of each urban context in the elaboration of these plans, part of this diagnosis being the assessment of environmental quality. The city of Teresina, capital of Piaui, grew under the bias of mechanistic urbanism, dissociated from systemic view, thus understanding the importance of studies in the area. This thesis proposes to evaluate the environmental quality of the area, currently understood by its center, added to the blocks that surpass it, covered by the first urban plan of the capital, from 1855. The study region was chosen because corresponds to the oldest urbanized area of the city, which has the presence of urban infrastructure equipment such as sewage, water supply, among other. The work presents as a method, initially, the bibliographic review followed by the field research. This consists of the analysis of environmental quality indicators, analysis of satellite images, with an interval of 10 years, and the elaboration of thematic maps, which associated generate the environmental quality map. It is hoped that this thesis will contribute with other related and to serve as a basis for proposing action goals on the spot.